2018
DOI: 10.1016/j.neuron.2018.02.020
|View full text |Cite
|
Sign up to set email alerts
|

A Basal Ganglia Circuit Sufficient to Guide Birdsong Learning

Abstract: Learning vocal behaviors, like speech and birdsong, is thought to rely on continued performance evaluation. Whether candidate performance evaluation circuits in the brain are sufficient to guide vocal learning is not known. Here, we test the sufficiency of VTA projections to the vocal basal ganglia in singing zebra finches, a songbird species that learns to produce a complex and stereotyped multi-syllabic courtship song during development. We optogenetically manipulate VTA axon terminals in singing birds conti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 88 publications
(150 reference statements)
6
90
0
Order By: Relevance
“…Light pulse delivery was dependent 382 on natural trial-to-trial variation in the pitch of the targeted syllable. In agreement with our previous results 383 (Xiao et al, 2018), we found that optogenetic excitation and inhibition elicited learned changes in the pitch 384 of the targeted syllable on future performances ( Figure 5C). In addition to changes in the pitch of the targeted 385 syllable, we found that phasic increases in dopamine also resulted in disruptions in song syntax similar to 386 birds in which we knocked down FoxP2 expression in Area X (Figures 5D, 5E and S7C), and phasic excitation 387 of dopaminergic terminals in Area X resulted in a significant increase in the number of times birds repeated 388 syllables at the beginning and/or end of their song motif ( Figures 5B, 5D and 5E).…”
Section: Knockdown Of Foxp2 Decreases Dopamine Receptor Expression Insupporting
confidence: 92%
See 4 more Smart Citations
“…Light pulse delivery was dependent 382 on natural trial-to-trial variation in the pitch of the targeted syllable. In agreement with our previous results 383 (Xiao et al, 2018), we found that optogenetic excitation and inhibition elicited learned changes in the pitch 384 of the targeted syllable on future performances ( Figure 5C). In addition to changes in the pitch of the targeted 385 syllable, we found that phasic increases in dopamine also resulted in disruptions in song syntax similar to 386 birds in which we knocked down FoxP2 expression in Area X (Figures 5D, 5E and S7C), and phasic excitation 387 of dopaminergic terminals in Area X resulted in a significant increase in the number of times birds repeated 388 syllables at the beginning and/or end of their song motif ( Figures 5B, 5D and 5E).…”
Section: Knockdown Of Foxp2 Decreases Dopamine Receptor Expression Insupporting
confidence: 92%
“…Recent studies have emphasized the idiosyncratic role of dopamine in 358 reward-based learning and the control of coordinated movements(Coddington and Dudman, 2019). We have 359 previously shown that acute manipulation of dopaminergic inputs to Area X does not affect ongoing vocal-360 motor actions but can instruct rapid bidirectional learned changes in song, consistent with reinforcement-361 based models for motor learning(Xiao et al, 2018). More broadly however, it is known that physical 362 manifestations of dopamine related impairments, like chorea or akinesia, can progressively develop with long 363 term disruptions in dopamine signaling(Chen et al, 2013).…”
mentioning
confidence: 73%
See 3 more Smart Citations